Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) -4x2 + 8x - 4
= - (4x2 - 8x + 4)
= - (2x - 2)2
b) -x52 + 10 x - 5
= - 5(x2 - 2x + 1)
= - 5(x - 1)2
Ta có
\(A=x^3-5x^2+8x-4=x^3-x^2-4x^2+4x+4x-4=x^2\left(x-1\right)-4x\left(x-1\right)+4\left(x-1\right)\)\(=\left(x^2-4x+4\right)\left(x-1\right)=\left(x-2\right)^2\left(x-1\right)\)
,2x^2-12x+18+2xy-6y
= 2(x^2-6x+9) + 2y(x-3)
= 2(x-3)^2 + 2y(x-3)
= (x-3)(2x-6+2y)
(x^2-6x+8)(x^2-8x+15)+1
=(x^2-4x-2x+8)(x^2-5x-3x+15)+1
=(x(x-4)-2(x-4))(x(x-5)-3(x-5))+1
=(x-4)(x-2)(x-5)(x-3)+1
=(x-2)(x-5)(x-3)(x-4)+1
=(x^2-7x+10)(x^2-7x+12)+1
Gọi a=x^2-7x+11, ta có
(a-1)(a+1)+1
= a2 - 1 + 1
= a2
= (x2 - 7x + 11)2
3{x-2}2/x{x-2}{x2+2x+4}=3{x-2}/x2+2x+4=-3/x+2
nho tick minh nha
\(\left(x+2\right)\left(x+3\right)\left(x+4\right)\left(x+5\right)-8=\left(x^2+7x+10\right)\left(x^2+7x+12\right)-8\)
Đặt \(x^2+7x=t\)
\(\left(t+10\right)\left(t+12\right)-8=t^2+22t+120-8\)
\(=t^2+22t+112=\left(t+8\right)\left(t+14\right)\)
Theo cách đặt \(=\left(x^2+7x+8\right)\left(x^2+7x+14\right)\)
\(8\text{x}^2+12\text{x}-4=4\left(2x^2+3\text{x}-1\right)\)